Kemampuan Berpikir Kreatif Siswa SMP dalam Menyelesaikan Soal Open-Ended - Lilis Setianingsih; Riawan Yudi Purwoko (JRPM (Jurnal Review Pembelajaran Matematika), 2019)
This study aims to determine students’ creative thinking skills to solve arithmetic progression and series with the open-ended method. The study uses a qualitative method with a case study approach. The subjects in this study were three students of junior high school have high mathematical abilities. Data were collected by tests, interviews, field notes, and documentation. Data were analyzed using the triangulation method to gain a deeper understanding of the subject under study. The results of this study show that the student's ability to creative thinking because it meets three indicators of creative thinking, namely fluency, flexibility, and novelty. For the research conducted to get good results, the subject should find answers that can be categorized in creative thinking indicators in the form of novelty.